Victimology: prevention of crimes against the life and health of a child - Polina, Zeleniak; Nataly, Kulakova; Stanislav, Mozol; Volodymyr, Dordiai; Nataliya, Mozol (Cuestiones Políticas, 2020)
The objective of the article is to propose a renewed protection system for children in the prevention of crimes against life and health. The research methodology is based on the combination of dialectical, formal, dogmatic, sociological, comparative law and documentary methods. The results of the study contributed to the development of measures to guarantee the safety of the child, which means a set of legal, economic, organizational measures, which are carried out by the public powers and the administration, with the aim of neutralizing and preventing usurpation of the life and health of children in Ukraine. Organizational and legal measures have been implemented to improve the interaction of the National Police with the services of children and special institutions for children by carrying out joint activities to prevent and identify possible invasions into the life and health of the child. It is concluded that in order to determine the characteristics of the subject, namely, crimes against the life and health of the child, it is necessary to improve the legislation in the interaction of the actors to prevent this type of crime.